The Effect of E-Service Quality and E-Trust on E-Customer Loyalty on Non-Cash Transaction Users of the Shopee Application Mediated by E-Satisfaction In Jambi Province - Astari,, Silvy; Latifa Arum (Adpebi Science Series, 2024)
This study aims to determine the Influence of E-Service Quality and E-Trust on E-Customer Loyalty of Non-Cash Transaction Users in the Shopee Application Mediated by E-Satisfaction in Jambi Province. The samplingtechnique uses a purposive sampling technique, using the Lemeshow formula so that a sample of 96 people was obtained.Research data collection techniques through online questionnaires (googe form) with a Likert scale. Based onthe results of the calculation using the Partial Least Square (PLS) research tool. The results of the research from the datatesting that have been carried out show that (1) E-Service Quality has a significant influence on E-Satisfaction,(2) E-Trust has a significant influence on E-Satisfaction. The results of the study on (3) E-Service Quality did not havea significant effect on E-Customer Loyalty. (4) E-Trust does not have a significant effect on E-Customer Loyalty. (5) E-Satisfaction has a significant influence on E-Customer Loyalty. As well as (6) E-Service Quality has a significantinfluence on E-Customer Loyalty through E-Satisfaction and (7) E-Trust has a significant influence on E-CustomerLoyalty through E-Satisfaction.This means that the variables e-service quality and e-trust can explain the e-satisfaction (Z) variable of non-cash transaction users in the Shopee application in Jambi Province by 70.7%, the remaining 29.3% is influenced by othervariables that are not observed in this study. Furthermore, the variables e-service quality and e-trust can also explain thee-customer loyalty (Y) variable of non-cash transaction users in the Shopee application in Jambi Province by 85.4% andthe remaining 14.6% influenced by other variables that are not observed in this study.